A Systematic Review of Pediatric Phase I Trials in Oncology: Toxicity and Outcomes in the Era of Targeted Therapies. (14th January 2020) - Cohen, Julia W.; Akshintala, Srivandana; Kane, Eli; Gnanapragasam, Helen; Widemann, Brigitte C.; Steinberg, Seth M.; Shah, Nirali N.
Abstract: Background: Pediatric phase I oncology trials have historically focused on safety and toxicity, with objective response rates (ORRs) <10%. Recently, with an emphasis on targeted approaches, response rates may have changed. We analyzed outcomes of recent phase I pediatric oncology trials. Materials and Methods: This was a systematic review of phase I pediatric oncology trials published in 2012–2017, identified through PubMed and EMBASE searches conducted on March 14, 2018. Selection criteria included full‐text articles with a pediatric population, cancer diagnosis, and a dose escalation schema. Each publication was evaluated for patient characteristics, therapy type, trial design, toxicity, and response. Results: Of 3, 431 citations, 109 studies (2, 713 patients) met eligibility criteria. Of these, 78 (72%) trials incorporated targeted therapies. Median age at enrollment/trial was 11 years (range 3–21 years). There were 2, 471 patients (91%) evaluable for toxicity, of whom 300 (12.1%) experienced dose‐limiting toxicity (DLT). Of 2, 143 patients evaluable for response, 327 (15.3%) demonstrated an objective response. Forty‐three (39%) trials had no objective responses. Nineteen trials (17%) had an ORR >25%, of which 11 were targeted trials and 8 were combination cytotoxic trials. Targeted trials demonstrated a lower DLT rate compared with cytotoxic trials (10.6% vs. 14.7%; p = .003) with similar ORRs (15.0% vs. 15.9%; p = .58). Conclusion: Pediatric oncology phase I trials in the current treatment era have an acceptable DLT rate and a pooled ORR of 15.3%. A subset of trials with target‐specific enrollment or combination cytotoxic therapies showed high response rates, highlighting the importance of these strategies in early phase trials. Implications for Practice: Enrollment in phase I oncology trials is crucial for development of novel therapies. This systematic review of phase I pediatric oncology trials provides an assessment of outcomes of phase I trials in children, with a specific focus on the impact of targeted therapies. These data may aid in evaluating the landscape of current phase I options for patients and enable more informed communication regarding risk and benefit of phase I clinical trial participation. The results also suggest that, in the current treatment era, there is a rationale to increase earlier access to targeted therapy trials for this refractory patient population. Abstract : This systematic review of pediatric oncology phase I trials describes the safety profile and response outcomes from recent trials, comparing cytotoxic and targeted trials in the era of targeted therapies.